Effectiveness of teaching strategies for engaging adults who experienced childhood difficulties in learning mathematics - Hasan, A.; Fraser, Barry (2013)
We investigated whether the introduction of a variety of activity-based teaching strategies into college-level mathematics classes in the United Arab Emirates was effective in terms of the nature of the classroom learning environment and students' satisfaction. In addition, we investigated how the use of personally-relevant and concrete activities changed the learning environment in ways that were perceived to be beneficial by adults who had experienced failure. For a sample of 84 students from eight classes in the Higher Colleges of Technology, the learning environment was assessed with a modified Arabic version of four scales (Involvement, Task Orientation, Personalisation and Individualisation) from the College and University Classroom Environment Inventory (CUCEI) and Satisfaction was also measured with a scale from the same instrument. As well, five case-study students were involved in assessing the learning environment through observations, semi-structured interviews and focus-group interviews in order to link qualitative information with the constructs assessed by the CUCEI. © 2013 Springer Science+Business Media Dordrecht.